Hybrid in situ product recovery technique applied to (A)IBE fermentation. (February 2018) - Pérez-Bibbins, B.; Gonzalez Peñas, H.; Toth, E.; Coupard, V.; Lopes-Ferreira, N.
Graphical abstract: Highlights: Gas stripping of IBE mixture is studied and operation conditions preconized. Hybrid technique (Gas Stripping + Liquid Extraction) is applied to IBE fermentation. Integrated technique leads to highest productivities and butanol extraction rate. Partial in situ regeneration of solvent phase is observed in hybrid system. Abstract: Fermentative production of alcohols is a promising alternative to petroleum-based fuels industry. However, the development of a competitive biological process implies the achievement of higher production titer and enhanced productivity. In the case of butanol production by solventogenic strains, In Situ Product Recovery (ISPR) techniques help to overcome the inhibition threshold of the microorganism and to reduce the overall cost of downstream process. In this work, gas stripping (GS) was preliminary studied in an abiotic system and high flow rates (vvm – vessel volume minute- >2 min −1 ) were needed to achieve higher butanol stripping rate than its production rate. Combined liquid extraction (LE) with pulse Gas Stripping (GS) were applied to batch fermentations resulting in a synergic effect giving a higher glucose consumption rate and a lower aqueous butanol concentration. Moreover, in this hybrid system, biphasic bioreactor acted as a "liquid–liquid equilibrium step" and both phases were stripped concomitantly.